Journal Economics, business & accountancy : INTENTION TO PURCHASE THE PRIVATE LABEL BRAND: THE ROLES OF FINANCIAL RISK PERCEPTION, PRICE, AND VALUE CONSCIOUSNESS FOR CONSUMERS OF HYPERMARKET IN SURA - Rahmawati, Veronika (PPPM Perbanas, 2013)
The consumers’ perception towards private label is considered important and therefore, it shouldbe understood by the retailers. This is true when related to the price and quality of private labels.In addition, these factors are the main consideration when the consumers purchase the privatelabel.